2015
DOI: 10.1111/ahg.12128
|View full text |Cite
|
Sign up to set email alerts
|

Ethnicity‐Based Differences in the Association of LOXL1 Polymorphisms with Pseudoexfoliation/Pseudoexfoliative Glaucoma: A Meta‐Analysis

Abstract: Pseudoexfoliation (PEX) is an age-related disorder of the extracellular matrix; it is strongly associated with glaucoma, the leading cause of irreversible blindness worldwide. We conducted an ethnic-based meta-analysis of the association of LOXL1 polymorphisms with PEX/pseudoexfoliative glaucoma (PEXG). Association studies were retrieved systematically from PubMed, EMBASE, and Web of Knowledge. Allelic and genotype frequencies of rs3825942, rs1048661, and rs2165241 were compared between PEX/PEXG and controls. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 66 publications
0
28
0
2
Order By: Relevance
“…In fact, in Greece, the prevalence of PEX is relatively high, maybe due to genetic reasons, since various polymorphisms were found to be associated with PEX in Greek population although environmental factors may also be implicated. [ 16 17 18 ] However, inadequate pupil dilation was not very common in our patient population with PEX, as it occurred in only one-quarter of the patients. Contrary to the present study, Drolsum et al .…”
Section: Discussionmentioning
confidence: 95%
“…In fact, in Greece, the prevalence of PEX is relatively high, maybe due to genetic reasons, since various polymorphisms were found to be associated with PEX in Greek population although environmental factors may also be implicated. [ 16 17 18 ] However, inadequate pupil dilation was not very common in our patient population with PEX, as it occurred in only one-quarter of the patients. Contrary to the present study, Drolsum et al .…”
Section: Discussionmentioning
confidence: 95%
“…11) and has been subsequently replicated by multiple studies in various geographical populations1213141516, it is currently not known how associated variants contribute to disease. So far, no single causal variant has been identified.…”
Section: Discussionmentioning
confidence: 99%
“…A genome-wide association study in Scandinavian populations identified lysyl oxidase-like 1 ( LOXL1 ) on chromosome 15q24.1 as a principal genetic risk factor for PEX syndrome/glaucoma11, a finding that has been replicated in multiple populations worldwide1213141516. Two common non-synonymous protein-coding variants in exon 1, rs1048661G>T (Arg141Leu) and rs3825942G>A (Gly153Asp), and one intronic variant (rs2165241T>C), conferring a 20-fold increased risk for PEX, were initially considered as the causal variants in this susceptibility locus.…”
mentioning
confidence: 99%
“…While genetic and environmental conditions may predispose to XFM formation or glaucoma, absence of concurrence of these risk factors across ethnic populations suggest clinical or local eye specific risk factors which may predispose to PXG or OHT. [ 1 , 8 – 12 ] While features of early stages or unmanifest stage of the disease is described which also includes radial pigments over the lens capsule,[ 2 , 3 ] specific clinical phenotypes which may signify a risk for developing OHT or future glaucoma in such phenotypic variants is unknown or not explored. This information would identify the risk of raised intraocular pressure or glaucoma in high-risk eyes allowing timely intervention and closer follow up.…”
Section: Introductionmentioning
confidence: 99%